Lyophilized amorphous dispersion of telmisartan in a combined carrier−alkalizer system: formulation development and in vivo study - AL-japairai, Khater Ahmed Saeed; Alkhalidi, Hala M.; Mahmood, Syed; Almurisi, Samah Hamed; Doolaanea, Abd Almonem; Al-Sindi, Taha A.; Chatterjee, Bappaditya (American Chemical Society, 2020)
Telmisartan suffers from low oral bioavailability due to its poor water solubility. The research work presents a formulation of solid dispersed (SD) telmisartan formulation as a ternary mixture of a drug, a polymeric carrier (poly-vinylpyrrolidone) (PVP) K30), and an alkalizer (Na2CO3). The preparation method, which was lyophilization of an aqueous solution containing the ingredients, was free from any organic solvent. The developed SD formulations resulted in a significant improvement in in vitro dissolution (>90% drug dissolution in 15 min) compared to pure telmisartan. Solid-state characterization by scanning electron microscopy (SEM), differential scanning calorimetry (DSC), and X-ray diffraction (XRD) studies indicated the conversion of crystalline telmisartan into an amorphous form. Fourier transform infrared (FTIR) spectroscopy revealed the drug−polymer interaction that was responsible for reducing the chances of recrystallization. A short-term stability study showed that selected SD formulations were stable in terms of in vitro dissolution and retained their amorphous structure in ambient and accelerated conditions over 2 months. Selected formulations (drug/PVP K30/Na2CO3 as 1:1:2 or 1:2:2 weight ratio) resulted in >2.48 times relative oral bioavailability compared to marketed formulations. It was considered that the incorporation of an alkalizer and a hydrophilic polymer, and amorphization of telmisartan by lyophilization, could enhance in vitro dissolution and improve oral bioavailability